Upregulation of ENAH by a PI3K/AKT/β-catenin cascade promotes oral cancer cell migration and growth via an ITGB5/Src axis - Chan, Xiu-Ya; Chang, Kai-Ping; Yang, Chia-Yu; Liu, Chiao-Rou; Hung, Chu-Mi; Huang, Chun-Chueh; Liu, Hao-Ping; Wu, Chih-Ching (Cellular & molecular biology letters, 2024)
Oral cancer accounts for 2% of cancer-related deaths globally, with over 90% of cases being oral cavity squamous cell carcinomas (OSCCs). Approximately 50% of patients with OSCC succumb to the disease within 5 years, primarily due to the advanced stage at which it is typically diagnosed. This underscores an urgent need to identify proteins related to OSCC progression to develop effective diagnostic and therapeutic strategies. To identify OSCC progression-related proteins, we conducted integrated proteome and transcriptome analyses on cancer tissues from patients and patient-derived xenograft (PDX) model mice. We investigated the role of protein-enabled homolog (ENAH), identified as an OSCC progression-associated protein, through proliferation, transwell migration, and invasion assays in OSCC cells. The mechanisms underlying ENAH-mediated functions were elucidated using gene knockdown and ectopic expression techniques in OSCC cells. ENAH was identified as a candidate associated with OSCC progression based on integrated analyses, which showed increased ENAH levels in primary OSCC tissues compared with adjacent noncancerous counterparts, and sustained overexpression in the cancer tissues of PDX models. We confirmed that level of ENAH is increased in OSCC tissues and that its elevated expression correlates with poorer survival rates in patients with OSCC. Furthermore, the upregulation of ENAH in OSCC cells results from the activation of the GSK3β/β-catenin axis by the EGFR/PI3K/AKT cascade. ENAH expression enhances cell proliferation and mobility by upregulating integrin β5 in oral cancer cells. The upregulation of ENAH through a PI3K/AKT/β-catenin signaling cascade enhances oral cancer cell migration and growth via the ITGB5/Src axis. These findings offer a new interpretation of the ENAH function in the OSCC progression and provide crucial information for developing new OSCC treatment strategies.